Analysis and overview of NQF developments in European countries : annual report 2012 - (:unkn) unknown (Publications Office of the European Union, 2013)
This fourth annual report on the development of national qualifications frameworks (NQFs) across Europe reveals that the rapid development and implementation of NQFs continued in 2012. "Most of the 36 countries working together on the European qualifications framework (the 27 EU member states as well as Croatia, the former Yugoslav Republic of Macedonia, Iceland, Liechtenstein, Montenegro, Norway, Serbia, Switzerland and Turkey) have now agreed on the overall structure of their frameworks. In addition to the fully operational frameworks in France, Ireland, Malta and the UK, 10 more are now entering an early operational phase. Frameworks are increasingly used to support incremental change in education and training. A significant development during 2012 is the opening up of NQFs to qualifications outside the formal, public system of qualifications, for example awarded by non-formal and private institutions and bodies. The 2012 overview shows that NQFs increasingly interact with and link to arrangements for validating non-formal and informal learning. The recent (December) agreement on the Council recommendation on validation of non-formal learning reflects the priority given to this area, inviting member states to put in place validation arrangements - linked to NQFs and in line with the EQF - by 2018. The progress made on NQFs has made it possible for more countries to complete their link to the EQF; 16 countries had linked their national qualifications levels to EQF levels by December 2012." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.2 Europa; EU-Bildungspolitik; Nationaler Qualifikationsrahmen; Europäischer Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Lebenslanges Lernen; Europäische Union; Kroatien; Mazedonien; Montenegro; Schweiz; Serbien; Türkei; Island; Liechtenstein; Norwegen